2015
DOI: 10.1007/s40279-015-0371-2
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Three Types of Exercise Interventions on Healthy Old Adults’ Gait Speed: A Systematic Review and Meta-Analysis

Abstract: BackgroundHabitual walking speed predicts many clinical conditions later in life, but it declines with age. However, which particular exercise intervention can minimize the age-related gait speed loss is unclear.PurposeOur objective was to determine the effects of strength, power, coordination, and multimodal exercise training on healthy old adults’ habitual and fast gait speed.MethodsWe performed a computerized systematic literature search in PubMed and Web of Knowledge from January 1984 up to December 2014. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
130
5
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 156 publications
(156 citation statements)
references
References 154 publications
(162 reference statements)
13
130
5
8
Order By: Relevance
“…By combining the body concentration and maintaining the proper body alignment, principle of Pilates stretch helps to stretch muscles in the complete range of motion needed for the muscle balance, and at the same time the contraction, that is done with the body support. Improvement of balance condition and walking speed was consistent with the results of Iwamoto et al (2009), but it contradicted by part of the results of a study which concluded that land endurance exercises did not have a significant effect on the walking speed (Hortobágyi et al, 2015). Although the nature of the training program used in the research is similar, the difference in the outcomes could be resulted from ignoring some factors such as the level of readiness of testers, physical activity level, motivation, gender, age, height, weight.…”
Section: Discussionsupporting
confidence: 64%
“…By combining the body concentration and maintaining the proper body alignment, principle of Pilates stretch helps to stretch muscles in the complete range of motion needed for the muscle balance, and at the same time the contraction, that is done with the body support. Improvement of balance condition and walking speed was consistent with the results of Iwamoto et al (2009), but it contradicted by part of the results of a study which concluded that land endurance exercises did not have a significant effect on the walking speed (Hortobágyi et al, 2015). Although the nature of the training program used in the research is similar, the difference in the outcomes could be resulted from ignoring some factors such as the level of readiness of testers, physical activity level, motivation, gender, age, height, weight.…”
Section: Discussionsupporting
confidence: 64%
“…Because of the diminished and increased contribution, respectively, by the ankle plantarflexors and hip extensors to the total mechanical output during gait [11] , we expect to find different correlations between gait speed and ankle plantarflexor (low correlation) versus hip extensor (high correlations) maximal voluntary torques in old adults. Such an expectation contrasts with the prevailing data that focused on the relationship between mobility and knee extensor function [10,14] even though old age has virtually no effects on knee kinetics measured during gait [10,11] .…”
mentioning
confidence: 64%
“…Our old adults' 1.5 m/s habitual gait speed is at the high end of habitual gait speed norms of 1.15 [26] , 1.24 [14] , and 1.30 m/s [27] as is the 2.0 m/s maximal gait speed (normal range: 1.44-1.99 m/s). Still, relative to the reference young adults group, old adults walked ∼ 12% slower with ∼ 11% shorter steps, had 18% lower leg LTM and were 34% weaker (all p < 0.05, Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Exercise is beneficial to physical and mental health and may prevent walking difficulty. [4][5][6] Communitybased group exercise programs are 1 option for promoting health and wellness and could potentially be used to improve walking in older adults. Studies examining the impact of group exercise prog r a m s o n w a l k i ng h a ve c o n f l i c t i ng f i n d i ng s a n d limitations.…”
mentioning
confidence: 99%